Cellular patterning of Arabidopsis roots under low phosphate conditions - Janes, George; von Wangenheim, Daniel; Cowling, Sophie; Kerr, Ian D.; Band, Leah R.; French, Andrew P.; Bishopp, Anthony (Frontiers, 2018)
Phosphorus is a crucial macronutrient for plants playing a critical role in many cellular signaling and energy cycling processes. In light of this, phosphorus acquisition efficiency is an important target trait for crop improvement, but it also provides an ecological adaptation for growth of plants in low nutrient environments. Increased root hair density has been shown to improve phosphorus uptake and plant health in a number of species. In several plant families, including Brassicaceae, root hair bearing cells are positioned on the epidermis according to their position in relation to cortex cells, with hair cells positioned in the cleft between two underlying cortex cells. Thus the number of cortex cells determines the number of epidermal cells in the root hair position. Previous research has associated phosphorus-limiting conditions with an increase in the number of cortex cell files in Arabidopsis thaliana roots, but they have not investigated the spatial or temporal domains in which these extra divisions occur or explored the consequences this has had on root hair formation. In this study, we use 3D reconstructions of root meristems to demonstrate that the anticlinal cell divisions seen under low phosphate are exclusive to the cortex. When grown on media containing replete levels of phosphorous, Arabidopsis thaliana plants almost invariably show 8 cortex cells; however when grown in phosphate limited conditions, seedlings typically develop 12-16 cortex cells, resulting in a significant increase in the number of epidermal cells at hair forming positions. These anticlinal divisions occur within the initial cells and can be seen within 24 hours of transfer of plants to low phosphorous conditions. We show that these changes in the underlying cortical cells feed into epidermal patterning by altering the regular spacing of root hairs.